1996
DOI: 10.3109/03005369609077925
|View full text |Cite
|
Sign up to set email alerts
|

Tympanometry and otoacoustic emissions in a cohort of special care neonates

Abstract: Otoacoustic emission (OAE) screening and oto-admittance testing (678 Hz probe tone) were performed on both ears of 84 special care neonates, as part of a larger study of middle-ear effusion in neonates and infants. OAE results, tympanometry, and acoustic reflex results are all strongly and significantly associated. No evidence was found of any maturational effects in the results. Based on the findings, a tentative classification scheme for neonatal tympanograms is suggested. We conclude that 678 Hz tympanometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 16 publications
3
32
0
1
Order By: Relevance
“…Using 1000 Hz probe tone tympanometry, a peaked tympanogram incidence of 93.4% was reported in 228 ears compared to 95% for neonates (1-4 weeks of age) in the current study. The 1000 Hz tympanometric peak results for neonates in the current study and those reported by Kei et al 16 are also similar to a 678 Hz probe tone study conducted on a group of 200 special care baby unit babies, which indicated a 91% incidence of discernible peak tympanograms 21 .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Using 1000 Hz probe tone tympanometry, a peaked tympanogram incidence of 93.4% was reported in 228 ears compared to 95% for neonates (1-4 weeks of age) in the current study. The 1000 Hz tympanometric peak results for neonates in the current study and those reported by Kei et al 16 are also similar to a 678 Hz probe tone study conducted on a group of 200 special care baby unit babies, which indicated a 91% incidence of discernible peak tympanograms 21 .…”
Section: Discussionsupporting
confidence: 76%
“…A significant but poorer sensitivity rate of 57% was obtained for both tympanometry and acoustic reflexes for correctly identifying middle ear pathology. The decreased sensitivity may in part be attributed to the presence of middle ear effusion in a number of ears with present but decreased OAEs 16,21 . Such cases result in an overlap of true positive high frequency immittance results and false negative OAE results and lead to decreased immittance sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results match the ones published 17 , which state that middle ear effusion could happen in 50% of neonate ears who fail hearing screening with OAEs.…”
supporting
confidence: 81%
“…The authors consider middle ear effusion as a severe and significant cause of OAEs hearing screening failure in newborns at the intensive care units. 17 The present investigation carried out with infants found a conductive alteration, confirmed by the otorhinolaryngological clinical evaluation and by the Brain Stem Auditory Evoked Potential in 75% of those who failed TEOAEs (study group).…”
Section: Discussionmentioning
confidence: 99%